Individual Characteristics, Adherence, and Barriers to Medication Adherence of Hypertensive Patients at the Indonesia - Timor Leste Border - Pius Almindu Leki Berek; Bambang Budi Siswanto; Dewi Irawati; Wisnu Jatmiko (Department of Nursing, Faculty of Medicine, Diponegoro University, 2022)
Background: Until the last decade, the incidence of hypertension has increased sharply. It has been reported that individuals with hypertension show a low level of adherence to their therapy management. Moreover, there has been no previous research evaluating individual characteristics, adherence, and barriers to medication adherence among people with hypertension at the border of Indonesia and Timor Leste.Purpose: This study aimed to identify individual characteristics, adherence, and barriers to medication adherence among hypertensive patients.Methods: A total of 112 hypertensive patients recruited using a quota sampling method at the border of Indonesia and Timor Leste participated in this cross-sectional study. Data were collected using the Hill-Bone Questionnaire to identify adherence and the Adherence Barrier Questionnaire (ABQ) to identify barriers to medication adherence. Individual characteristics were also collected. To confirm the hypertension condition at the time of data collection, measurements of blood pressure were retaken. Descriptive statistics and Chi-square analysis were used for data analysis. Results: The average of systolic blood pressure was 163.85(18.24) mmHg, and the diastolic blood pressure was 99.30(11.57) mmHg. The Chi-square test showed that education and occupation had a significant relationship with adherence (p<0.05) and barriers to medication adherence (p=0.000). Meanwhile, other characteristics, including age, gender, and marital status, were not significantly related to adherence (p>0.05) and barriers to medication adherence (p>0.05).Conclusion: There is a relationship between education and occupation with adherence and barriers to medication adherence, but there is no relationship when viewed from such individual characteristics as age, gender, and marital status. Further research is needed to identify effective educational methods to increase the knowledge, motivation, and self-efficacy of hypertensive patients to improve blood pressure control.